2008
DOI: 10.3141/2088-13
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Trajectory-Based Calibration Approach of Car-Following Models in Presence of Measurement Errors

Abstract: Interest in calibration of car-following models by using real-life microscopic trajectory data is increasing. However, more information is needed on the influence of methodological issues on calibration results as well as on the influence of practical issues related to the use of real-life data. In particular, the influence of measurement errors on parameter estimates has not yet been considered in detail. To gain insight into the influence of measurement errors on calibration results, synthetic data were crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 17 publications
0
60
0
Order By: Relevance
“…The approach allows combining multiple sources of data, thereby improving the estimation results when the information in individual trajectories is limited (Ossen & Hoogendoorn 2008). Possible data sources are:…”
Section: Introductionmentioning
confidence: 99%
“…The approach allows combining multiple sources of data, thereby improving the estimation results when the information in individual trajectories is limited (Ossen & Hoogendoorn 2008). Possible data sources are:…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is often supposed that the independent variables are measured exactly and only the dependent variable has errors associated with measurement. However, the observed data will always contain measurement errors [9,14,15]. More and more studies indicated that measurement errors-in-variables (EIV) can yield a considerable bias in the estimation results and consequently reduce reliability of the models [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed data will always contain measurement errors [9,14,15]. More and more studies indicated that measurement errors-in-variables (EIV) can yield a considerable bias in the estimation results and consequently reduce reliability of the models [9,14,15]. This paper chooses the Van Aerde model to demonstrate the improvement for calibration of the car-following model by considering measurement errors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations